DIREITOS AUTORAIS COMO INSTITUTO DE PROTEÇÃO DOS CONHECIMENTOS TRADICIONAIS INDÍGENAS - Raquel Rosan Christino Gitahy; Joyce Camargo Fukushima (Universidade do Oeste Paulista, 2009)
The objective of the present article was to argue the participation of the indian in the formation of the cultural identity of the Brazilian society, considering mainly its cultural production and the changes in the legislation how much to the protection and consolidation of politics that assure the social and cultural diversity. For the accomplishment of the displayed objective a bibliographical research was effected. The research in the verification of the application of the copyrights in the peculiar case of the Brazilian aboriginal peoples from a questioning on the difficulties faced for the jurists to take this clarification to the communities. As a focus was the quarrel regarding the relevance of the application of the copyrights as half to assure the aboriginal cultural identity, associating: copyrights, the importance of the protection to the traditional knowledge and the relevance of the register of the incorporeal patrimony of the aboriginal culture. As results we verify that while the formularization of a more complete law is waited and specific that has led, in consideration, the main peculiarities of the aboriginal peoples, the Brazilian population must extend its social vision regarding the native cultures in order to brighten up the politics of homogenization of the society. The studied authors demonstrate the absence in the legal system of a special protection to the traditional knowledge, becoming necessary that the professional of the right opts to adapting the legislation of copyright to these cases.